A concordância com adjetivos pós-nominais em expressões nominais coordenadas com apenas um determinante - Gramacho, Carolina (Revista da Associação Portuguesa de Linguística, 2019)
This paper provides a corpus-based study of agreement with post-nominal adjectives in coordinate nominal expressions with only one determiner in European Portuguese (EP). It aims to provide clues to understand the patterns of agreement that contradict the predictions of our previous studies in which we made a distinction between two constructions corresponding to the same categorial linear outputs: (a) those associated with the reference of only one entity and (b) those in which nouns are used to refer distinct entities. Since it was suggested by those previous studies the existence of parallel patterns of agreement between Spanish and EP in these types of constructions, we aim to provide a preliminary comparative study that allow us to explore this possibility, namely in what concerns the closest conjunct agreement in both gender and number (considering the different behaviors of the values of these features). Finally, we aim to evaluate the adequacy of some proposals presented for Spanish to explain the EP data, contributing to the description of these structures and presenting some clues for further investigation.